Brazilian Society of Surgical Oncology considerations on gynecologic cancer management during COVID-19 pandemic - Glauco Baiocchi; Eid Gonçalves Coelho; Thales Paulo Batista; Gustavo Guitmann; Paulo Henrique de Sousa Fernandes; Reitan Ribeiro; Heber Salvador de Castro Ribeiro; Alexandre Ferreira Oliveira; Audrey Tieko Tsunoda (Brazilian Journal of Oncology)
The present proposal aims to support and help clinicians how to manage gynecologic cancer patients during the COVID-19 pandemic. It is based on the opinions of surgical oncologists of the Brazilian Society of Surgical Oncology (BSSO) and not necessarily evidence-based instructions.